2018
DOI: 10.1021/acs.langmuir.7b03668
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Antimicrobial Mechanisms of Surface-Immobilized Peptides in Situ

Abstract: Antimicrobial peptides (AMPs) in free solution can kill bacteria by disrupting bacterial cell membranes. Their modes of action have been extensively studied, and various models ranging from pore formation to carpet-like mechanisms were proposed. Surface-immobilized AMPs have been used as coatings to kill bacteria and as sensors to capture bacteria, but the interaction mechanisms of surface-immobilized AMPs and bacteria are not fully understood. In this research, an analytical platform, sum frequency generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…The antibacterial activity of the peptides was associated with the change of their orientation upon interaction with bacteria, i.e., the bacterium-induced peptide bending inflicts damage to the bacteria. 304 This behavior differs from the surface-immobilized behavior of the cecropin P1 peptide (see section 3.2.2).…”
Section: Wlbu2mentioning
confidence: 93%
“…The antibacterial activity of the peptides was associated with the change of their orientation upon interaction with bacteria, i.e., the bacterium-induced peptide bending inflicts damage to the bacteria. 304 This behavior differs from the surface-immobilized behavior of the cecropin P1 peptide (see section 3.2.2).…”
Section: Wlbu2mentioning
confidence: 93%
“…Costa et al and Barbosa et al showed the importance of peptide attachment site in covalent immobilization on antimicrobial activity [14,15,22]. hLF (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and Dhvar-5 possess a head-to-tail amphipathicity that probably promotes distinctive interactions with bacteria. In this work, we showed that the antimicrobial activity of the Ī±-helical MSI-78(4-20) peptide was not affected by attachment site upon immobilization onto chitosan films, probably due to the distribution of the hydrophobic and hydrophilic amino acids along the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…However, AMPsā€™ activity may be influenced by several factors, such as solid supports, spacer specificities, surface density, exposure, orientation, and peptide stability [ 4 ]. Several Ī±-helical AMPs have already been immobilized on different surfaces using a variety of conditions, and results show that their efficacy may depend on the terminus chosen to tether the peptide to the surface, as this may lead to exposure of termini with different characteristics or induce different AMP conformations and orientation on the surface [ 10 , 11 , 12 , 13 ]. MSI-78, the parent peptide, was previously immobilized on alkyne-terminated self-assembled monolayers through both its C - and N - termini.…”
Section: Introductionmentioning
confidence: 99%
“…However, as shown in Figure 7, the orientation of AMPs changes after their initial interaction with bacteria (i.e., the immobilized Ī±-helices bind to the anionic lipid bilayer). Since immobilized AMPs cannot follow the barrel-stave or toroidal model due to limited mobility, it is suggested that the charge-charge interaction plays a dominant role in the elimination of bacteria [104,105]. Additionally, when functionalizing the material's surface with different reactive groups as seen in Figure 8, the orientation of immobilized AMPs can be controlled using chemo-selective (i.e., directed immobilization) coupling reactions.…”
Section: Orientation Of Direct Immobilized Ampsmentioning
confidence: 99%